The Northern Norway Mother-and-Child Contaminant Cohort Study (MISA): Population Characteristics, Dietary Intake and Predictors of Organochlorine Contaminants in Meconium and Maternal Serum, and of Essential and Toxic Elements in Mothers’ Whole Blood - Veyhe, Anna Sofía (UiT The Arctic University of Norway, 2016)
Paper II of this thesis is not available in Munin: Is meconium useful to predict fetal exposure to organochlorines and hydroxylated PCBs? Veyhe A.S. et al. Available in Environmental Science Processes & Impacts, 2013 Aug;15(8):1490-500 Persistent Organic Pollutants (POPs) and toxic elements are released into the environment and are carried to the Arctic area via the atmosphere, oceanic currents and rivers. They have the ability to accumulate in nature and bioconcentrate in the human food chain. The primary exposure route for these contaminants is through diet, and thus circulating levels in pregnant women can give an indication of the potential risk to the developing fetus. Within countries and internationally, guidelines for safe daily intakes and for concentrations in serum or whole blood have been established to avoid health effects of POPs and toxic inorganic elements. In this context, the rationale for the MISA study was to assess exposure to a suite of environmental pollutants by women during pregnancy and to six weeks postpartum, as well of the unborn/ newborn children. Through a detailed questionnaire information was obtained on food intake (past and present), lifetime residency, education, income and other sociodemographic data, obstetrical history and pregnancy outcome. The specific aim of the thesis was to explore the links between maternal diet and selected personal and obstetrical characteristics with concentrations of PCBs (and hydroxylated metabolites) and organochlorine (OC) pesticides in maternal serum and in newborn first stool, as well as with a selection of essential and toxic metals in maternal whole blood. Of the 515 enrolled women, 391 completed the study protocol that included a self-administrated food frequency questionnaire (FFQ) and donation of biological samples for analyses. The FFQ information was converted into daily intake of energy, micro- and macro-nutrients. Findings were compared to a drop-out group (n = 113) and, when possible, to all delivering women from Northern ...